PENGUATAN PERAN PAWANG UTEUN SEBAGAI LEMBAGA ADAT DALAM PENANGGULANGAN PEMBALAKAN LIAR MELALUI INTEGRASI HUKUM ADAT DAN HUKUM NEGARA DI KABUPATEN ACEH UTARA - Wiranti; Sawaluddin Siregar; Misbah Mardia; Roni Sahindra (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2026)
Illegal logging is a significant environmental issue in North Aceh Regency, which not only damages ecosystems but also threatens the livelihoods of communities dependent on natural resources. This study aims to analyze the role of Pawang Uteun, an indigenous institution, in combating illegal logging through the integration of customary law and state law. The Pawang Uteun plays a crucial role in regulating and conserving adat forests based on longstanding indigenous norms. Using a qualitative approach, this research gathers data through in-depth interviews with indigenous leaders, government officials, and local communities, as well as relevant literature review. The findings show that while state laws and regulations exist to address illegal logging, their implementation is often hindered by institutional limitations and resource constraints. In contrast, the customary law applied by Pawang Uteun has proven effective in managing forest use and engaging the community in direct oversight. The integration of customary law and state law strengthens the position of Pawang Uteun in combating illegal logging by providing socially accepted sanctions and fostering active participation in forest protection. This study recommends strengthening cooperation between indigenous institutions and the state to enhance monitoring of illegal logging and preserve adat forests, which are vital for the community's survival.